Associations of Life's Simple 7 With Cerebral Small Vessel Disease. Issue 9 (17th August 2022) - Liu, Dandan; Cai, Xueli; Yang, Yingying; Wang, Suying; Yao, Dongxiao; Mei, Lerong; Jing, Jing; Li, Shan; Yan, Hongyi; Meng, Xia; Li, Hao; Wei, Tiemin; et al.
Abstract : Background: The purpose of this study is to examine the associations of Life's Simple 7 (LS7) with risks of cerebral small vessel disease (CSVD) and its magnetic resonance imaging markers. Methods: Community-dwelling residents in Lishui city in China from the cross-sectional survey of the PRECISE study (Polyvascular Evaluation for Cognitive Impairment and Vascular Events) were included in this study from 2017 to 2019. LS7 was analyzed as the total score, medical score (derived from the 3 metrics based on medical history and testing), and behavioral score (based on 4 metrics based on behaviors), and categorized as poor, intermediate, or ideal. A CSVD score or a modified CSVD score was derived from 4 magnetic resonance imaging markers (lacunes, microbleeds, perivascular spaces, and white matter hyperintensity) at baseline. Binary logistic regression or ordinal logistic regression model was used to estimate the relationship of LS7 scores with CSVD and magnetic resonance imaging markers. Results: A total of 3061 participants were included in this study. Compared with poor total LS7 score, ideal LS7 total score was associated with reduced adjusted odds of higher CSVD score (common odds ratio [cOR], 0.73 [95% CI, 0.58–0.90]) and higher modified CSVD score (cOR, 0.78 [95% CI, 0.64–0.95]). Compared with poor LS7 medical score, ideal LS7 medical score was associated with reduced adjusted odds of higher CSVD score (cOR, 0.65 [95% CI, 0.53–0.80]) and higher modified CSVD score (cOR, 0.67 [95% CI, 0.56–0.81]). Higher total LS7 score and LS7 medical score were associated with a lower risk of white matter hyperintensities and lacunes. Higher LS7 behavioral score was associated with lower risk of lacunes. Conclusions: Ideal LS7 score, indicating excellent cardiovascular health, was associated with lower total CSVD burden. Optimizing the risk factors captured by LS7 may reduce the progression of CSVD.